Inland dry season saline intrusion in the Vietnamese Mekong River Delta is driving the identification and implementation of alternative crops to rice. (April 2023) - Kaveney, Brooke; Barrett-Lennard, Edward; Chau Minh, Khoi; Dang Duy, Minh; Nguyen Thi, Kim Phuong; Kristiansen, Paul; Orgill, Susan; Stewart-Koster, Ben; Condon, Jason
Abstract: CONTEXT: Inland saline intrusion is occurring during the dry season in the Mekong River Delta (MRD), Vietnam. Rising sea levels, tidal fluctuations, drought, and changes to upstream flow contribute to extensive salinisation of rice producing areas of the MRD, leading to substantial rice crop losses. OBJECTIVE: The identification, evaluation and implementation of alternative crop and soil management solutions are required to complement on-going rice production in the region. METHODS: A review of scientific and grey literature was conducted regarding the nature and extent of salinisation in the MRD and the adoption and management of alternative crops to rice. RESULTS: Familiar crops in Vietnam (e.g., maize, soybean), as well as novel crops to the MRD (e.g., quinoa, cowpea) were explored as potential options to replace dry season rice. Management options including surface soil mulches and plastic coverings help maintain soil moisture and reduce salinity damage to plants, and the use of drainage and seed preparation techniques can improve plant establishment and yield. Factors contributing to the success of alternative crops include salt tolerance, timing and efficiency of water use, ability to grow in the dry growing season, tolerance to pests and diseases, labour intensiveness and the crops' marketability. SIGNIFICANCE: The identification of suitable alternative crops to replace dry season rice in saline affected areas of the MRD, combined with management practices like mulching and soil moisture monitoring, could provide farmers with income opportunities to offset rice losses. Documenting the factors contributing to successful crop diversification can assist with decision-making and support initiatives among farmers, agribusiness, and government agencies. Graphical abstract: Dry season saline intrusion in the Mekong River Delta is requiring the identification of suitable alternative crop and soil managment options for farmers. Unlabelled Image Highlights: Inland saline intrusion is causing substantial rice losses during the dry season of the Mekong River Delta, Vietnam. Alternative crops and management practices need to be identified to supplement the loss of rice income. Numerous biophysical, environmental, and socioeconomic factors are identified that determine alternative crops suitability. Mulching, raised beds and soil water monitoring can decrease salinity stress and improve water use efficiency. Combining alternative crops and management practices provide farmers with options for saline affected areas.